Airway macrophages as the guardians of tissue repair in the lung. Issue 3 (15th February 2019) - Puttur, Franz; Gregory, Lisa G; Lloyd, Clare M
Abstract: The lungs present a challenging immunological dilemma for the host. Anatomically positioned at the environmental interface, they are constantly exposed to antigens, pollutants and microbes, while simultaneously facilitating vital gas exchange. Remarkably, the lungs maintain a functionally healthy state, ignoring harmless inhaled proteins, adapting to toxic environmental insults and limiting immune responses to allergens and pathogenic microbes. This functional strategy of environmental adaptation maintains immune defense, reduces tissue damage, and promotes and sustains lung immune tolerance. At steady state, airway macrophages produce low levels of cytokines, and suppress the induction of innate and adaptive immunity. These cells are primary initiators of lung innate immunity and possess high phagocytic activity to clear particulate antigens and apoptotic cell debris from the airways to regulate the response to infection and inflammation. In response to epithelial injury, resident and recruited macrophages drive tissue repair. In this review, we will focus on the functional importance of macrophages in tissue homeostasis and inflammation in the lung and highlight how environmental cues alter the plasticity and function of lung airway macrophages. We will also discuss mechanisms employed by pulmonary macrophages to promote resolution of tissue inflammation, and how and when this balance is perturbed, they contribute to pathological remodeling in acute and chronic infections and diseases such as asthma, idiopathic pulmonary fibrosis and chronic obstructive pulmonary disease. Abstract : Airway macrophages are important guardians of pulmonary homeostasis. They are primary immune sentinels critical in regulating the balance between immune cell defense against pathogens and tolerance toward innocuous stimuli. Airway macrophages promote resolution of tissue inflammation but when this balance is perturbed they contribute to pathological remodeling in acute and chronic infections and diseases such as asthma, idiopathic pulmonary fibrosis and chronic obstructive pulmonary disease.